The END : A New Indicator of Financial and Nonfinancial Corporate Sector Vulnerability - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2005)
This paper describes a corporate sector vulnerability indicator, the expected number of defaults (END), based on the joint occurrence of defaults among a number of firms and/or institutions. The END indicator is general enough to assess systemic risk in the corporate and financial sectors, as well as systemic sovereign risk; and is also forward looking as it is constructed using information implied by financial securities prices. Using equity prices and balance-sheet data, we calculate the END to assess systemic risk in the corporate sector in Korea, Malaysia, and Thailand. We also discuss how the END systemic risk indicator overcomes some of the shortcomings of other vulnerability indicators.